IDENTIFICATION AND RISK ASSESSMENT IN CARSHARING - Andrzej HANUSIK (Scientific Journal of Silesian University of Technology. Series Transport)
There are many new concepts for doing business in the modern market. Carsharing is one of such models that are directly related to the sharing economy. The current body of literature shows an absence of reports about risk management in carsharing operators. Further investigation of scientific databases confirms the existence of a research gap in this field. The purpose of this article is for identification of risks in carsharing and their latter assessment in terms of probability of occurrence, impact on customer relationships, the importance of a given category and the cost they generate. A way of aggregating various categories of risks into one synthetic indicator to prioritise them was proposed. The methodology of the process was based on a methodological triangulation which is established on the following studies – analysis and criticism of literature which helps to place discussed research problems on a theoretical basis, qualitative research and observations allowing to identify individual categories of risks and quantitative research enabling the description of given categories of risks by appropriate variables on which further risk modelling is performed. Such research may be a basis for subsequent analysis and an impulse to an academic debate. Besides, it may contribute to the creation of further studies, which deal with the problem of assessment of the risk in concepts related to sharing economy.